2018
DOI: 10.1111/aos.13847
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a patient‐derived questionnaire for treatment of neovascular age‐related macular degeneration: dimensions of importance in treatment of neovascular age‐related macular degeneration

Abstract: This study provides a brief patient-derived questionnaire, expressed with a score with good psychometric performance that can be used for monitoring during intravitreal injection treatment of nAMD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Dimensions of Importance in Treatment of neovascular Age-related Macular Degeneration (DITAMD) is a questionnaire measuring the satisfaction of important dimensions during intravitreal injection treatment 30. DITAMD contains 15 dimensions: (1) receive treatment to preserve vision; (2) information about your diagnosis and treatment; (3) waiting time at the clinic; (4) trust in those treating you; (5) accommodating staff; (6) follow-up structure; (7) planning of treatment consultations; (8) treatment continuity; (9) good pain relief during injection treatment; (10) injection technique to reduce discomfort during treatment; (11) transport/travel challenges back and forth from the eye clinic; (12) good hygiene during treatment; (13) receive early access to treatment after referral; (14) involvement in treatment decisions; (15) information about possible visual aids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimensions of Importance in Treatment of neovascular Age-related Macular Degeneration (DITAMD) is a questionnaire measuring the satisfaction of important dimensions during intravitreal injection treatment 30. DITAMD contains 15 dimensions: (1) receive treatment to preserve vision; (2) information about your diagnosis and treatment; (3) waiting time at the clinic; (4) trust in those treating you; (5) accommodating staff; (6) follow-up structure; (7) planning of treatment consultations; (8) treatment continuity; (9) good pain relief during injection treatment; (10) injection technique to reduce discomfort during treatment; (11) transport/travel challenges back and forth from the eye clinic; (12) good hygiene during treatment; (13) receive early access to treatment after referral; (14) involvement in treatment decisions; (15) information about possible visual aids.…”
Section: Methodsmentioning
confidence: 99%
“…They gave comments and advice regarding study information and questionnaires. One of the four questionnaires used in the study, DITAMD, was developed in partnership with nAMD patients 30. Patients that responded to the questionnaires in current study also gave their opinion on the relevance of each questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the experience of living with AMD (5,6,9,10) highlighted the potential importance of factors such as the acceptance of the disease and its consequences for vision, fears regarding disease progression and medical treatment, the way medical treatment and prognosis are communicated to patient, the communication between patient and health care-professionals, pre-conceptions on AMD, and quality of social support. A recent study conducted with wet AMD patients (11) revealed key patient dimensions related to treatments and living with the disease, such as receive treatment to preserve vision, waiting time at the clinic, information about the diagnosis and treatment, trust in healthcare professionals, preserving vision, early access to treatment, pain relief, and visual aids. An ethnographic study exploring patients' perspectives of geographic atrophy (12), an advanced form of AMD, highlighted the negative impact of the disease on people's daily functioning, particularly in basic and essential activities such as reading, driving, watching movies, and negative interference with hobbies.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies highlighted the need to develop tailored psychosocial interventions to address specific mental health needs of adults with AMD (9,43). Mental health needs in AMD patients are commonly associated with the impact of losing sight and losing independence (10,44,45), fears of uncertainty with regard to prognosis (10,44), anxiety associated with the diagnosis and medical treatments (9), coping with a chronic medical condition (10), burden related to regular hospital visits (9,11,12), and lack of social support (28). Additionally, in some AMD patients, particularly in patients with wet AMD, their mental health needs might not be exclusively linked to visual impairment, as these patients can have their vision preserved by medical treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation